The 8Ps Marketing Mix and the Buyer Decision-Making Process - Parmer, Lucinda L.; Dillard, Jr., John E.; Lin, Ying-Chou (Journal of Marketing Development and Competitiveness, 2023)
The 8 Ps marketing mix consists of (1) service product; (2) price; (3) place; (4) promotion; (5) people; (6) process; (7) physical evidence; and (8) productivity (Booms & Bitner, 1980; 1981). The buyer decisionmaking process consists of five stages to include (1) need recognition; (2) information search; (3) evaluation of alternatives; (4) purchase decision; and (5) post-purchase evaluation (Dewey, 1910; Engel, et al., 1978; 1986). This paper utilized a sample size of 426 participates to examine these two constructs of the 8 Ps marketing mix and the decision-making process, along with the socio-demographics of age; gender; ethnicity; socio-economic level; and education level. Tukey’s Honest Significant Difference PostHoc Analysis found multiple significant relationships (p < .05).